Comparative Evaluation of the Remineralizing Efficacy of Fluoride Varnish and its Combination Varnishes on White Spot Lesions in Children with ECC: A Randomized Clinical Trial - Radha, Sarangapani (Int J Clin Pediatr Dent, 2020)
AIM: The aim of the study was to assess the remineralizing efficacy of fluoride and its combination varnishes on white spot lesion (WSL) in children with early childhood caries (ECC). MATERIALS AND METHODS: Sixty children with active WSL on primary maxillary anterior teeth were randomly selected. At baseline, the WSL activity was evaluated using ICDAS II [lesion activity assessment (LAA)] and its dimensions through photographic method. They were allocated to group I (GI) (5% NaF), group II (GII) [5% NaF with amorphous calcium phosphate (ACP)], and group III (GIII) [5% NaF with casein phosphopeptides – amorphous calcium phosphate (CPP –ACP)]. First, oral hygiene instructions and diet counseling were given followed by application of fluoride varnishes in their respective groups. The same parameters were recorded at follow-up of 2, 4, 12, and 24 weeks intervals. Data were collected and subjected to statistical analysis using Friedman Chi-square and Mann–Whitney tests. RESULTS: Overall, the active WSL changed to inactive over a period of 24 weeks in GI was 90%, GII was 95%, and 100% in GIII. There was a significant reduction in dimension of WSL in GI from 4.119 to 2.525 (p = 0.0001). Likewise, there was a significant reduction in dimension of WSL in GII and GIII from 4.586 to 3.258 and 4.696 to 1.2155, respectively (p = 0.0001, p = 0.0001). Comparatively, group III (MI varnish) showed statistically significant reduction in the dimension of WSL from baseline to 24 weeks (p = 0.002). But the results were statistically insignificant with change of active lesions to its inactivity (p = 0.349). CONCLUSION: Fluoride varnish with CPP–ACP was found to be an effective preventive strategy in reversing WSL in children with ECC. CLINICAL RELEVANCE: These combination varnishes could prove to be a promising preventive measure for pediatric dentists in reversing white spot lesions of ECC. CLINICAL TRIAL REGISTRY: NCT03360266. HOW TO CITE THIS ARTICLE: Radha S, Kayalvizhi G, Adimoulame S, et al. Comparative Evaluation of the Remineralizing Efficacy of Fluoride Varnish and its Combination Varnishes on White Spot Lesions in Children with ECC: A Randomized Clinical Trial. Int J Clin Pediatr Dent 2020;13(4):311–317.